1987
DOI: 10.1007/bf02200995
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: Follow-up study of 148 patients. I: Classification, clinical and laboratory findings, course and outcome

Abstract: The present paper is a description of 148 patients with circulating antinuclear antibodies and multisystemic disease filed during 18 years by one of the authors and followed up to date in 1981-83. Seventy-eight per cent of the patients satisfied the 1971 ARA criteria for the classification of systemic lupus erythematosus and 92 per cent fulfilled the 1982 ARA criteria. Eighty-five per cent were women, the mean age at onset of SLE was 32 years. Malar rash and arthritis were early manifestations in 80 per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Survival rates in this cohort were generally lower than those reported in other studies of survival in patients with SLE. Among studies published since 1980, the 5-year and 10-year survival estimates averaged 87% and 86%, respectively (7)(8)(9)(10)(11)(12)1422). In the 3 previous studies that reported 15-year survival estimates, these estimates averaged 79% (7,16,19).…”
Section: Discussionmentioning
confidence: 97%
“…Survival rates in this cohort were generally lower than those reported in other studies of survival in patients with SLE. Among studies published since 1980, the 5-year and 10-year survival estimates averaged 87% and 86%, respectively (7)(8)(9)(10)(11)(12)1422). In the 3 previous studies that reported 15-year survival estimates, these estimates averaged 79% (7,16,19).…”
Section: Discussionmentioning
confidence: 97%
“…In recent decades the treatment and life expectancy of SLE patients have been significantly improved. 2,4,17,18 Despite that, evidence suggests that the quality of this extended life can remain poor compared with that of the general population and worse than that of individuals with other chronic diseases. 19,20 In the majority of patients the disease is no longer an acute life-threatening disease but a chronic one.…”
Section: Definitions Of Remission Prolonged Remission and A Cure In Slementioning
confidence: 99%
“…The natural history of the disease is characterised by episodes of relapses, 'flares', interchanging with remissions, and the outcome is highly variable ranging from permanent remission to death. Important co-morbidity is caused by infections and thromboembolic episodes [2,3]. The age of the patients at onset may significantly influence the course of the disease [4,5].…”
Section: Introductionmentioning
confidence: 99%